2019
DOI: 10.1136/bmjdrc-2019-000824
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal visceral and subcutaneous adipose tissues in association with cardiometabolic risk in children and adolescents: the China Child and Adolescent Cardiovascular Health (CCACH) study

Abstract: ObjectiveTo investigate the association of abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) with cardiometabolic risk factors in children and adolescents.Research design and methodsThis cross-sectional study consisted of 8460 children and adolescents aged 6–18 years from Chinese urban areas who underwent dual-energy X-ray absorptiometry scan and had metabolic risk factors measured.ResultsIn multivariate analysis adjusted for region, family income, age, puberty development, physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
1
17
3
Order By: Relevance
“…The epididymal adipose tissue represents subcutaneous fat pad, while the perirenal tissue represents abdominal visceral fat pad. It has been reported that hypotrophy of visceral fat is the risk for cardiovascular diseases development, while subcutaneous fat accumulation is a relatively protective factor which encounters excess energy intake (25). Epididymal and perirenal adipose tissue samples were usually taken to determine the wet weight of the fat pad and body fat ratio in the absence of dual-energy X-ray absorptiometry (DEXA) (26).…”
Section: Discussionmentioning
confidence: 99%
“…The epididymal adipose tissue represents subcutaneous fat pad, while the perirenal tissue represents abdominal visceral fat pad. It has been reported that hypotrophy of visceral fat is the risk for cardiovascular diseases development, while subcutaneous fat accumulation is a relatively protective factor which encounters excess energy intake (25). Epididymal and perirenal adipose tissue samples were usually taken to determine the wet weight of the fat pad and body fat ratio in the absence of dual-energy X-ray absorptiometry (DEXA) (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that central fat includes trunk and android fat (23), and the ndings indicate that higher fat mass in the he trunk and android fat plays an important role in the progression of CVRFs in children and adolescents (24). Other ndings suggested that arms and legs fat mass confer differential cardiometabolic risk in subjects.…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of CVRFs increased with the percentile of all body fat mass. Previous study found that central fat includes trunk and android fat (23), and the ndings indicate that higher fat mass in the he trunk and android fat plays an important role in the progression of CVRFs in children and adolescents (24). Other ndings suggested that arms and legs fat mass confer differential cardiometabolic risk in subjects.…”
Section: Discussionmentioning
confidence: 84%